Characterization and suitability evaluation of rice growing soils for sustainable land use planning using geographic information system (GIS) - MOHAN, M. MADHAN; M.V.S., NAIDU; REDDY, G. PRABHAKARA (Journal of Soil and Water Conservation, 2026)
Ten typical representative pedons from rice growing soils of Tirupati revenue division, Chittoor, Andhra Pradesh were characterized for crop suitability evaluation by limitations methods using GIS. The soils were deep (>1.0 m), sandy clay loam to sandy loam texture and clay, silt and sand ranged from 13.6 to 45.4, 9.4 to 28.1 and 38.5 to 71.6 per cent. The bulk density ranged from 1.28 to 1.80 Mg m-3 and increased with depth. The water holding capacity ranged from 27.2 to 52.9 per cent and negatively correlated with sand (r = -0.863). The soils were neutral to strongly alkaline (7.32 to 9.32), non- saline to slightly saline (0.22 to 5.62 dS m-1) and low to high organic carbon (3.9-11.7 g kg-1). The cation exchange capacity, base saturation and ESP ranged from low to medium (9.24 to 29.24 cmol (p+) kg-1), medium to high (63.5 to 85.7%) and 0.15 to 16.75 per cent. The available N was low to medium (40.9 to 388.9 kg ha-1), available P2O5 and K2O were 6.5 to 178.6 kg ha-1 and 42.5 to 642.8 kg ha-1 (low to high). The available sulphur was 3.7 to 35.5 mg kg-1 and micro nutrients were sufficient except Zn in some soil profiles. Based on crop suitability evaluation, soils were highly suitable for groundnut, sunflower, sugarcane and finger millet cultivation with an area of 24068, 3898, 16303 and 16303 ha. representing 72.6, 11.2, 49.2 and 49.2, per cent. Moderately suitable for rice, maize, groundnut sunflower, sesame, sugarcane and finger millet cultivation with an area of 33144, 33144, 9066, 29246, 33144, 16840 and 16841 ha. representing 100, 100, 27.4, 88.8, 100, 50.8 and 50.8 per cent of study area.